Method for improving step lines on surface of 3D printed product

By using ink mixture mixed with high and low cohesive energy compounds in 3D printing, the problem of step markings on the inclined surface of 3D printed products is solved, and the accuracy and flatness of the product surface is improved.

CN119463410APending Publication Date: 2025-02-18SHANGHAI BIJIE ADDITIVE DIGITAL TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411638243.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-16
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

3D printing is prone to step marks when printing beveled or curved surfaces, which affects the accuracy and roughness of the product surface, and thus affects the overall quality of the printed product.

Method used

Using a method of improving the surface step pattern of 3D printed products, the powder bed nozzle and ink jet head are used to perform layer by layer bonding and curing by loading powder material and ink mixture into a 3D printing device. The ink mixture includes a mixture of binder, nanoparticles, solvents and high and low cohesive energy compounds, and the mass ratio of high and low cohesive energy compounds is (3-5): 1.

Benefits of technology

Through the high diffusion amplitude and adhesive properties of the ink mixture, the adhesive forms a parabolic structure at the inclined surface, reducing the dripping of the bonded material, weakening the step pattern phenomenon, and improving the accuracy and flatness of the printed product.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005137675390000081
    Figure BDA0005137675390000081
  • Figure BDA0005137675390000091
    Figure BDA0005137675390000091
Patent Text Reader

Abstract

The invention relates to the technical field of additive binder spray forming, and particularly discloses a method for improving step lines on the surface of a 3D printing product. The method for improving the surface step lines of the 3D printing product comprises the following specific steps that a powder material and ink mixture is loaded into 3D printing equipment, a powder bed spray head on the 3D printing equipment is used for conducting powder bed laying operation, an ink jet head is used for conducting ink jet operation, and after a layer of powder bed is laid, the ink jet head conducts ink jet around the edge of the laid powder bed. The ink mixture sprayed by the ink jet head has high diffusion amplitude and bonding capacity and can be firmly adhered to the inclined plane of a printed product in a water drop shape, dripping of the bonding material is reduced, a parabola structure is formed at the step pattern, and then the step pattern phenomenon is weakened.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of additive binder jetting, and more specifically, to a method for improving step lines on the surface of 3D printed products. Background Art

[0002] 3D printing, also known as additive manufacturing, selectively sprays binders at corresponding positions according to the two-dimensional data of the cross section at the set height of the model, and finally forms layers through the penetration of the binder. In this way, a layer of granular material is laid, flattened and compacted, and then a layer of binder is sprayed, and the cycle is repeated until the entire object is bonded. It has the advantages of fast processing of large solid parts, good hardness and compressive resistance of the parts, and is widely used in the manufacture of functional equipment in many fields.

[0003] However, during the 3D printing powder laying process, when printing inclined surfaces or curved surfaces, step marks are likely to appear on the curved surfaces and gradient deformation surfaces of the 3D printed sand cores, affecting the accuracy and roughness of the product surface, and thus affecting the overall quality of the printed products, and even resulting in unqualified products. Summary of the invention

[0004] In order to improve the phenomenon of step lines on 3D printed products, the present application provides a method for improving step lines on the surface of 3D printed products.

[0005] The present application provides a method for improving step lines on the surface of a 3D printed product, using the following technical solution: A method for improving step lines on the surface of a 3D printed product, comprising the following specific steps: The powder material and ink mixture are loaded into the 3D printing device, and the powder bed is laid by using the powder bed nozzle on the 3D printing device, and the inkjet head is used for inkjet operation. After laying a layer of powder bed, the inkjet head sprays ink around the edge of the laid powder bed, and the operation is repeated to bond and solidify layer by layer to obtain a 3D printed product; The ink mixture includes the following raw materials in parts by weight: 40-60 parts of a binder, 20-30 parts of nanoparticles, 10-20 parts of a solvent, and 3-5 parts of an ink regulator. The ink regulator is a mixture of a high cohesive energy compound and a low cohesive energy compound, and the mass ratio of the high cohesive energy compound to the low cohesive energy compound is (3-5):1.

[0006] By adopting the above technical solution, the ink mixture can be firmly adhered to the inclined surface of the printed product in the shape of a water droplet by utilizing the strong diffusion range and adhesion of the ink mixture, thereby reducing the dripping of the adhesive material, forming a parabolic structure at the step pattern, and thus weakening the step pattern phenomenon.

[0007] High cohesive energy compounds and low cohesive energy compounds are selected and compounded in a suitable ratio to form an ink regulator. The strong intermolecular force of the high cohesive energy compound is used to promote the binder to be firmly adsorbed on the surface of the printed product, forming a parabolic structure at the step pattern, thereby weakening the step pattern phenomenon. The flow regulation performance of low cohesive energy is used to promote the ink mixture to have a better diffusion effect on the steps of each layer of the printed product, reduce the roughness of the printed product, and then weaken the step pattern phenomenon. High cohesive energy compounds increase the cohesive energy of the binder, reduce the dripping of the binder, promote the ink mixture to adhere firmly to the step pattern, present a certain parabolic structure, thereby weakening the step pattern phenomenon of the 3D printed product and improving the accuracy of the printed product.

[0008] Preferably, the high cohesive energy compound is at least one of propylene glycol, ethylene glycol and polyethylene glycol, and the low cohesive energy compound is glycerol.

[0009] By adopting the above technical solution, the high cohesive energy compound can combine with the binder, reduce the overflow and dripping of the binder, and promote the binder to be firmly bonded to the surface of each layer of the printed product, weakening the step pattern phenomenon. Using a small amount of low cohesive energy compound glycerol can adjust the rheological properties of the ink mixture, promote the ink mixture to be evenly sprayed on the surface of the printed product, improve the flatness and uniformity of the surface of the printed product, and thus reduce the generation of step patterns.

[0010] Preferably, the binder is furan resin.

[0011] By adopting the above technical scheme, furan resin has good heat resistance, strength and rigidity, can maintain stable bonding force, can be filled in the pores and step lines on the surface of printed products, reduce the shrinkage deformation of printed products, enhance the bonding strength between layers of printed products, improve the step line phenomenon of printed products, and improve the 3D printing accuracy.

[0012] Preferably, the furan resin comprises the following raw materials in parts by weight: 20-30 parts of phenolic resin, 40-50 parts of sugar alcohol, 3-5 parts of polyacid, 10-20 parts of graphene, and 0.3-0.5 parts of sodium stearate.

[0013] By adopting the above technical solution, graphene can form a cross-linked network structure in furan resin, enhance the bonding performance of furan resin, enable furan resin to firmly adhere to the step lines of printed products, reduce the phenomenon of conventional adhesives easily dripping, and improve the step line phenomenon of printed products.

[0014] Preferably, the ink mixture further includes 5-8 parts of glass fiber and 1-3 parts of zinc oxide.

[0015] By adopting the above technical solution, the addition of zinc oxide and glass fiber can effectively fill the pores generated by the ink mixture during solidification and shrinkage, and promote the ink mixture to stably adhere to the surface of each layer of the printed product, forming a certain parabolic structure, weakening the step pattern phenomenon, and improving the hardness and dimensional stability of the printed product.

[0016] Preferably, the glass fiber and zinc oxide are both modified with a silane coupling agent.

[0017] By adopting the above technical scheme, after the glass fiber and zinc oxide are treated with the silane coupling agent, the silane coupling agent can be used as a bridge to promote the glass fiber and zinc oxide to be evenly dispersed in the ink mixture, and can be firmly combined with the binder to reduce the dripping of the binder on the printed product, and can promote the ink mixture to firmly adhere to the surface of each layer of the printed product, thereby improving the accuracy of the printed product.

[0018] Preferably, the particle size of the nanoparticles is 100-300 nm.

[0019] Preferably, the nanoparticles are at least one of ceramic powder, sand powder and gypsum powder.

[0020] By adopting the above technical solution, ceramic powder, sand powder, and gypsum powder are added to the ink mixture, which can enhance the strength and hardness of the ink mixture and improve the wear resistance and impact resistance of the printed product. Ceramic powder, sand powder, and gypsum powder fill the pores between the layers of the printed product, improve the smoothness and uniformity of the surface of the printed product, and then reduce the formation of step lines, making the surface of the printed product smoother and more delicate. At the same time, ceramic powder, sand powder, and gypsum powder can increase the rheology of the ink mixture, which can make the ink mixture sprayed more evenly on the printed product, reduce the phenomenon of conventional single adhesives easily dripping and overflowing, and reduce the appearance of step lines.

[0021] Preferably, the solvent is one of water, ethanol and dimethylformamide.

[0022] In summary, this application has the following beneficial effects: 1. Since the present application uses a combination of high and low cohesive energy compounds and a binder, the cohesive energy of the binder can be improved, which enables the ink mixture to adhere firmly to the surface of each layer of the printed product, reduces the dripping and overflow of the binder, and utilizes the adsorption and diffusion effects of the ink mixture to form a parabolic structure with a certain curvature at the step pattern, thereby weakening the step pattern phenomenon.

[0023] 2. In this application, furan resin is used as a binder, which can enhance the bonding strength and rigidity of the ink mixture and reduce the shrinkage of the binder during curing. At the same time, an appropriate amount of graphene is added to the furan resin raw material to enhance the network structure of the furan resin, reduce the dripping and overflow of the binder, improve the surface flatness and uniformity of the printed product, and reduce the step pattern phenomenon. DETAILED DESCRIPTION

[0024] The present application is further described in detail below with reference to the embodiments.

[0025] The average particle size of graphene is 1-10 μm.

[0026] The molecular weight of the phenolic resin is 2000.

[0027] Preparation Example of Furan Resin Preparation Example 1 The furan resin comprises the following raw materials in parts by weight: 25 kg of phenolic resin, 45 kg of sugar alcohol, 4 kg of polyacid, 15 kg of graphene, and 0.4 kg of sodium stearate, wherein the polyacid is oxalic acid and the sugar alcohol is mannitol.

[0028] The preparation method of furan resin comprises the following specific steps: The phenolic resin, sugar alcohol, graphene and sodium stearate were mixed and dissolved in acetone, the temperature was raised to 40°C and mixed evenly, and then polyacid was added and the temperature was continued to be raised to 100°C for reaction. After the reaction for 1 hour, the temperature was lowered and the furan resin was filtered to obtain.

[0029] Preparation Example 2 The difference between Preparation Example 2 and Preparation Example 1 is that the amount of phenolic resin used in the furan resin raw material is 20 kg, the amount of sugar alcohol used is 50 kg, the amount of polyacid used is 3 kg, the amount of graphene used is 10 kg, and the amount of sodium stearate used is 0.3 kg.

[0030] Preparation Example 3 The difference between Preparation Example 3 and Preparation Example 1 is that the amount of phenolic resin used in the furan resin raw material is 30 kg, the amount of sugar alcohol used is 40 kg, the amount of polyacid used is 5 kg, the amount of graphene used is 20 kg, and the amount of sodium stearate used is 0.5 kg.

[0031] Preparation Example 4 The difference between Preparation Example 4 and Preparation Example 1 is that no graphene is used in the furan resin raw material.

[0032] Preparation Example of Ink Mixture Preparation Example 5 The ink mixture includes the following raw materials in parts by weight: 50 kg of a binder, 25 kg of nanoparticles, 15 kg of a solvent, and 4 kg of an ink regulator; wherein the ink regulator is a mixture of a high cohesive energy compound and a low cohesive energy compound in a mass ratio of 4:1, the high cohesive energy compound is propylene glycol, the low cohesive energy compound is glycerol, the binder is a furan resin, the furan resin comes from Preparation Example 1, the nanoparticles are ceramic powder, the average particle size of the ceramic powder is 100-300 nm, and the solvent is water.

[0033] The method for preparing the ink mixture comprises the following specific steps: The binder, nanoparticles, ink regulator and solvent are mixed and stirred evenly to prepare an ink mixture.

[0034] Preparation Example 6 The difference between Preparation Example 6 and Preparation Example 5 is that the mass ratio of the high cohesive energy compound to the low cohesive energy compound in the ink mixture raw material is 3:1.

[0035] Preparation Example 7 The difference between Preparation Example 7 and Preparation Example 5 is that the mass ratio of the high cohesive energy compound to the low cohesive energy compound in the ink mixture raw material is 5:1.

[0036] Preparation Example 8 The difference between Preparation Example 8 and Preparation Example 5 is that the amount of binder used in the ink mixture raw material is 40 kg, the amount of nanoparticles used is 20 kg, the amount of solvent used is 10 kg, and the amount of ink regulator used is 3 kg.

[0037] Preparation Example 9 The difference between Preparation Example 9 and Preparation Example 5 is that the amount of binder used in the ink mixture raw material is 40 kg, the amount of nanoparticles used is 20 kg, the amount of solvent used is 10 kg, and the amount of ink regulator used is 3 kg.

[0038] Preparation Example 10 The difference between Preparation Example 10 and Preparation Example 5 is that the high cohesive energy compound in the raw material of the ink mixture is ethylene glycol.

[0039] Preparation Example 11 The difference between Preparation Example 11 and Preparation Example 5 is that the high cohesive energy compound in the ink mixture raw material is a mixture of polyethylene glycol and propylene glycol, and the mass ratio of polyethylene glycol to propylene glycol is 1:1.

[0040] Preparation Example 12 The difference between Preparation Example 12 and Preparation Example 5 is that the nanoparticles in the raw material of the ink mixture are a mixture of gypsum powder and sand powder, the mass ratio of gypsum powder to sand powder is 1:1, and the average particle size of the nanoparticles is 100-300nm.

[0041] Preparation Example 13 The difference between Preparation Example 13 and Preparation Example 5 is that the binder in the raw materials of the ink mixture comes from Preparation Example 2.

[0042] Preparation Example 14 The difference between Preparation Example 14 and Preparation Example 5 is that the binder in the raw materials of the ink mixture comes from Preparation Example 3.

[0043] Preparation Example 15 The difference between Preparation Example 15 and Preparation Example 5 is that the binder in the raw materials of the ink mixture comes from Preparation Example 4.

[0044] Preparation Example 16 The difference between Preparation Example 16 and Preparation Example 5 is that the ink mixture raw materials also include 7 kg of glass fiber and 2 kg of zinc oxide.

[0045] The method for preparing the ink mixture comprises the following specific steps: The binder, glass fiber, zinc oxide, nanoparticles, ink regulator and solvent are mixed and stirred evenly to prepare an ink mixture.

[0046] Preparation Example 17 The difference between Preparation Example 17 and Preparation Example 16 is that the glass fiber and zinc oxide in the ink mixture raw materials are modified by a silane coupling agent, wherein the silane coupling agent is KH-560.

[0047] The method for preparing the ink mixture comprises the following specific steps: S1: Mix the silane coupling agent with water in advance to prepare a treatment liquid with a mass fraction of 1.5% of the silane coupling agent, then mix the treatment liquid with glass fiber and zinc oxide, the mass ratio of the sum of the mass of the glass fiber and zinc oxide to the treatment liquid is 10:1, heat treatment is carried out at 70°C for 2h, then take out the glass fiber and zinc oxide, wash and dry them, and the modification treatment of the glass fiber and zinc oxide is completed.

[0048] S2: Mixing the modified glass fiber and zinc oxide with a binder, nanoparticles, an ink regulator and a solvent, stirring them evenly to prepare an ink mixture.

[0049] Preparation Example 18 The difference between Preparation Example 18 and Preparation Example 17 is that the amount of glass fiber used in the ink mixture raw material is 5 kg, and the amount of zinc oxide used is 3 kg.

[0050] Preparation Example 19 The difference between Preparation Example 19 and Preparation Example 17 is that the amount of glass fiber used in the ink mixture raw material is 8 kg, and the amount of zinc oxide used is 1 kg.

[0051] Preparation Example 20 The difference between Preparation Example 20 and Preparation Example 5 is that no ink regulator is used in the ink mixture raw materials.

[0052] Preparation Example 21 The difference between Preparation Example 21 and Preparation Example 5 is that the ink regulator in the ink mixture raw material is a low cohesive energy compound. Example

[0053] Example 1 This embodiment provides a method for improving step lines on the surface of a 3D printed product, including the following specific steps: The powder material and ink mixture are loaded into the 3D printing equipment, the powder material is stone powder, and the ink mixture comes from Preparation Example 5. The powder bed is laid by the powder bed nozzle on the 3D printing equipment, and the inkjet head is used for inkjet operation. After laying a layer of powder bed, the inkjet head sprays ink around the edge of the laid powder bed. The operation is repeated to bond and solidify each layer to obtain a 3D printed product.

[0054] Example 2 The difference between Example 2 and Example 1 is that the ink mixture in the method for improving the step patterns on the surface of 3D printed products comes from Preparation Example 6.

[0055] Example 3 The difference between Example 3 and Example 1 is that the ink mixture in the method for improving the step patterns on the surface of 3D printed products comes from Preparation Example 7.

[0056] Example 4 The difference between Example 4 and Example 1 is that the ink mixture in the method for improving the step patterns on the surface of 3D printed products comes from Preparation Example 8.

[0057] Example 5 The difference between Example 5 and Example 1 is that the ink mixture in the method for improving the step patterns on the surface of 3D printed products is derived from Preparation Example 9.

[0058] Example 6 The difference between Example 6 and Example 1 is that the ink mixture in the method for improving the step patterns on the surface of 3D printed products comes from Preparation Example 10.

[0059] Example 7 The difference between Example 7 and Example 1 is that the ink mixture in the method for improving the step patterns on the surface of 3D printed products comes from Preparation Example 11.

[0060] Example 8 The difference between Example 8 and Example 1 is that the ink mixture in the method for improving the step patterns on the surface of 3D printed products comes from Preparation Example 12.

[0061] Example 9 The difference between Example 9 and Example 1 is that the ink mixture in the method for improving the step patterns on the surface of 3D printed products comes from Preparation Example 13.

[0062] Example 10 The difference between Example 10 and Example 1 is that the ink mixture in the method for improving the step patterns on the surface of 3D printed products comes from Preparation Example 14.

[0063] Embodiment 11 The difference between Example 11 and Example 1 is that the ink mixture in the method for improving the step patterns on the surface of 3D printed products comes from Preparation Example 15.

[0064] Example 12 The difference between Example 12 and Example 1 is that the ink mixture in the method for improving the step patterns on the surface of 3D printed products is derived from Preparation Example 16.

[0065] Embodiment 13 The difference between Example 13 and Example 1 is that the ink mixture in the method for improving the step patterns on the surface of 3D printed products comes from Preparation Example 17.

[0066] Embodiment 14 The difference between Example 14 and Example 1 is that the ink mixture in the method for improving the step patterns on the surface of 3D printed products is derived from Preparation Example 18.

[0067] Embodiment 15 The difference between Example 15 and Example 1 is that the ink mixture in the method for improving the step patterns on the surface of 3D printed products is derived from Preparation Example 19.

[0068] Comparative Example Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that the ink mixture in the method for improving the step patterns on the surface of 3D printed products comes from Preparation Example 20.

[0069] Comparative Example 2 The difference between Comparative Example 2 and Example 1 is that the ink mixture in the method for improving the step patterns on the surface of 3D printed products comes from Preparation Example 21.

[0070] Comparative Example 3 The difference between Comparative Example 3 and Example 1 is that in the method for improving the step patterns on the surface of the 3D printed product, an equal amount of a binder is used instead of the ink mixture, and the binder is furan resin, which is derived from Preparation Example 1.

[0071] Performance testing According to the method for improving the step lines on the surface of 3D printed products provided in Examples 1-15 and Comparative Examples 1-3 of the present application, a sloped product with an inclination angle of 60 degrees was printed, and then the 3D printed product was tested for the following performance. The specific test results are shown in Table 1.

[0072] Detection Methods 1. Appearance of printed products The step patterns and smoothness of the surface of the 3D printed product prepared in the present application were observed with the naked eye.

[0073] 2. Printing accuracy test After the 3D printed product prepared in the present application was degreased and sintered, the density of the 3D printed product was measured using the Archimedes drainage method, and the volume shrinkage of the 3D printed product before and after sintering was measured using a vernier caliper.

[0074] 3. Strength test Referring to the standard of GB / T3354-2014 "Test method for tensile properties of oriented fiber reinforced polymer matrix composite materials", the tensile strength of the printed product prepared in this application was tested, and the tensile rate was 2 mm / min.

[0075] Table 1: Performance test data table It can be seen from the performance test results that the present application forms an ink mixture by compounding an ink regulator and a binder, which can be added to the inclined surfaces of each layer of the printed product. By utilizing the molecular force and diffusion ability of the high cohesive energy compounds of the ink regulator, it can firmly adhere to the step lines and form a parabolic structure, thereby weakening the step line phenomenon.

[0076] By comparing Example 11 with Example 1, it can be seen that in Example 11, graphene is not added to the binder, and the strength of the printed product prepared is significantly reduced, and the bonding performance of the ink mixture is significantly reduced, which further proves that graphene can enhance the cross-linking strength of the ink mixture system, promote the ink mixture to be more firmly bonded to the surface of the product, and reduce the step pattern phenomenon.

[0077] In Examples 13-15, appropriate amounts of glass fiber and zinc oxide are added to the ink mixture, and a silane coupling agent is also used for modification. From the performance test results, it can be seen that the deformation rate of the printed product is significantly reduced, the dimensional stability is improved, and the strength is also enhanced. It is further explained that adding glass fiber and aluminum oxide to the ink mixture can improve the density of the printed product and reduce the generation of step lines. By comparing Example 12 with Example 13, it can be seen that in Example 12, no silane coupling agent is used to modify the glass fiber and zinc oxide, and the improvement of the comprehensive performance of the printed product is limited.

[0078] By comparing Comparative Examples 1 and 2 with Example 1, it can be seen that Comparative Example 1 does not use an ink regulator, and Comparative Example 2 does not use a high cohesive energy compound. From the performance test results, it can be seen that the surface of the printed product has obvious step lines, and the precision of the printed product is significantly reduced. It further illustrates that the use of high cohesive energy compounds can reduce the dripping of the binder, and at the same time, when combined with low cohesive energy compounds, it can adjust the rheological properties of the ink mixture and improve the uniformity and flatness of the surface of the printed product. A single low cohesive energy compound has limited effect on improving the bonding stability of the binder.

[0079] By comparing Comparative Example 3 with Example 1, it can be seen that in Comparative Example 3, only an adhesive is sprayed on the surface of the printed product, and an equal amount of furan resin is used instead of the step-grain adhesive, wherein no other components such as nanoparticle components are added. From the performance test results, it can be seen that although a large amount of adhesive can enable the printed product to have a certain strength, obvious adhesive overflow and dripping phenomena occur on the surface of the printed product, and there is also a relatively obvious step-grain phenomenon, which further illustrates that a single adhesive is likely to reduce the precision of the printed product and cannot improve the step-grain phenomenon on the surface of the printed product.

[0080] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A method for improving step lines on the surface of a 3D printed product, characterized in that: The specific steps include: The powder material and ink mixture are loaded into the 3D printing device, and the powder bed is laid by using the powder bed nozzle on the 3D printing device, and the inkjet head is used for inkjet operation. After laying a layer of powder bed, the inkjet head sprays ink around the edge of the laid powder bed, and the operation is repeated to bond and solidify layer by layer to obtain a 3D printed product; The ink mixture comprises the following raw materials in parts by weight: 40-60 parts of a binder, 20-30 parts of nanoparticles, 10-20 parts of a solvent, and 3-5 parts of an ink regulator. The ink regulator is a mixture of a high cohesive energy compound and a low cohesive energy compound, and the mass ratio of the high cohesive energy compound to the low cohesive energy compound is (3-5):

1.

2. The method for improving step lines on the surface of 3D printed products according to claim 1, characterized in that: The high cohesive energy compound is at least one of propylene glycol, ethylene glycol and polyethylene glycol, and the low cohesive energy compound is glycerol.

3. The method for improving step lines on the surface of 3D printed products according to claim 1, characterized in that: The binder is furan resin.

4. The method for improving step lines on the surface of 3D printed products according to claim 3, characterized in that: The furan resin comprises the following raw materials in parts by weight: 20-30 parts of phenolic resin, 40-50 parts of sugar alcohol, 3-5 parts of polyacid, 10-20 parts of graphene, and 0.3-0.5 parts of sodium stearate.

5. The method for improving step lines on the surface of 3D printed products according to claim 1, characterized in that: The ink mixture also includes 5-8 parts of glass fiber and 1-3 parts of zinc oxide.

6. The method for improving step lines on the surface of 3D printed products according to claim 5, characterized in that: The glass fiber and zinc oxide are both modified by a silane coupling agent.

7. The method for improving step lines on the surface of 3D printed products according to claim 1, characterized in that: The particle size of the nanoparticles is 100-300 nm.

8. The method for improving step lines on the surface of 3D printed products according to claim 7, characterized in that: The nanoparticles are at least one of ceramic powder, sand powder and gypsum powder.

9. The method for improving step lines on the surface of 3D printed products according to claim 1, characterized in that: The solvent is one of water, ethanol and dimethylformamide.